Secondary battery and manufacturing method thereof
Patent Information
- Application Number
- JP2024539058
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-14
- Filing Date
- 2023-01-13
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-01-13
AI Technical Summary
【0012】 本発明による二次電池は、垂直方向に積層された複数の電極と前記電極の間にそれぞれ介在された複数のセパレータを含む電極組立体およびゲルポリマー電解質を含み、前記セパレータに含まれるセラミックコーティング層が、無機物粒子およびバインダーを特定の含量で含むことを特徴とする。前記セパレータに含まれるセラミックコーティング層は、バインダーを少ない含量で含むことから、バインダー過量による抵抗の増加が防止されることができ、このような抵抗の低減に伴われる二次電池のセル剛性の低下を前記ゲルポリマー電解質が補完することができる。したがって、本発明による二次電池は、上記の構成の組み合わせにより、二次電池の抵抗低減と、セル剛性および機械的耐久性を同時に向上させることができる。
Smart Images

Figure 2025500563000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0006028 filed on January 14, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a secondary battery and a method for manufacturing the same. [Background technology]
[0003] 2. Description of the Related Art Along with technological development and increasing demand for electronic devices, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries having high energy density and voltage have been commercialized and are widely used.
[0004] The secondary battery may be manufactured, for example, by housing an electrode assembly in which electrodes and separators are alternately stacked in a battery case, injecting an electrolyte into the battery case, and sealing the battery case.
[0005] Here, the separator is generally formed by forming ceramic coating layers containing inorganic particles and a binder on both sides of a porous substrate. Here, the binder is generally contained in a large amount to easily bond the electrode and the separator, but in this case, there are problems that the resistance increases due to the excessive use of the binder and the energy density of the battery decreases due to the increase in the thickness of the separator.
[0006] Meanwhile, if the binder content in the ceramic coating layer included in the separator is reduced to prevent the above problems, there is a risk of quality degradation, such as a decrease in the adhesion between the electrodes and the separator, which reduces the rigidity of the cell and causes the electrodes to become misaligned.
[0007] In this respect, there is a need to develop a secondary battery that simultaneously reduces the resistance of the secondary battery and improves the cell rigidity. Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to solve the above-mentioned problems and to provide a secondary battery in which the resistance of the secondary battery is reduced and at the same time the cell rigidity and mechanical durability are improved.
[0009] Another object of the present invention is to provide a method for producing a secondary battery in which the resistance of the secondary battery is reduced and the cell rigidity and mechanical durability are improved at the same time. [Means for solving the problem]
[0010] The present invention provides a secondary battery comprising an electrode assembly, a gel polymer electrolyte, and a battery case housing the electrode assembly and the gel polymer electrolyte, the electrode assembly comprising a plurality of electrodes and a plurality of separators, the plurality of electrodes being stacked vertically, each of the plurality of separators being interposed between the stacked electrodes, the separator comprising a porous substrate and a ceramic coating layer disposed on both sides of the porous substrate, the ceramic coating layer comprising 92 wt % or more and less than 100 wt % of inorganic particles and more than 0 wt % and 8 wt % or less of a binder.
[0011] The present invention also provides a method for manufacturing a secondary battery, the method including the steps of: housing an electrode assembly in the battery case; injecting a gel polymer electrolyte composition into the battery case; curing the gel polymer electrolyte; and sealing the battery case, the electrode assembly including a plurality of electrodes and a plurality of separators, the plurality of electrodes being stacked vertically, each of the plurality of separators being interposed between the stacked electrodes, the separator including a porous substrate and a ceramic coating layer disposed on both sides of the porous substrate, the ceramic coating layer including 92 wt % or more and less than 100 wt % of inorganic particles and more than 0 wt % and 8 wt % or less of a binder. Effect of the Invention
[0012] The secondary battery according to the present invention includes an electrode assembly including a plurality of electrodes stacked vertically and a plurality of separators respectively interposed between the electrodes, and a gel polymer electrolyte, and the ceramic coating layer included in the separator includes inorganic particles and a binder in a specific content. Since the ceramic coating layer included in the separator includes a small content of binder, an increase in resistance due to an excessive amount of binder can be prevented, and the gel polymer electrolyte can compensate for the decrease in cell rigidity of the secondary battery that accompanies such a decrease in resistance. Therefore, the secondary battery according to the present invention can simultaneously reduce the resistance of the secondary battery and improve the cell rigidity and mechanical durability by combining the above-mentioned components.
[0013] In addition, the method for manufacturing a secondary battery according to the present invention is a method for manufacturing a secondary battery including an electrode assembly including a plurality of vertically stacked electrodes and a plurality of separators interposed between the electrodes, and a gel polymer electrolyte, characterized in that the ceramic coating layer included in the separator includes inorganic particles and a binder in a specific content. Since the ceramic coating layer included in the separator includes a small content of binder, an increase in resistance due to an excessive amount of binder can be prevented, and the gel polymer electrolyte can compensate for the decrease in cell rigidity of the secondary battery that accompanies such a decrease in resistance. Therefore, the secondary battery manufactured by the method for manufacturing a secondary battery according to the present invention can simultaneously reduce the resistance of the secondary battery and improve the cell rigidity and mechanical durability by combining the above-mentioned components. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic side view of a secondary battery according to an embodiment of the present invention; [Diagram 2] 2 is a schematic side view of an electrode assembly included in a secondary battery according to an embodiment of the present invention; [Diagram 3]2 is a schematic side view of a separator included in a secondary battery according to one embodiment of the present invention; [Figure 4] 4 is a schematic side view of an electrode assembly according to another embodiment of the present invention; [Diagram 5] 11 is a plan view of a separator or electrode illustrating adhesive application marks included in a secondary battery according to another embodiment of the present invention; FIG. [Figure 6] 11 is a schematic side view of an electrode assembly included in a secondary battery according to still another embodiment of the present invention. [Figure 7] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention. [Figure 8] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention. [Figure 9] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention. [Figure 10] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention. [Figure 11] 1A to 1C are diagrams illustrating a method for manufacturing a secondary battery according to the present invention. [Figure 12] 3 is a photograph of the surface of a separator included in the secondary battery of Example 1. [Figure 13] 4 is a photograph of the surface of a separator included in the secondary battery of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0016] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50) can be measured, for example, by using a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.
[0017] Hereinafter, the secondary battery of the present invention will be described in detail with reference to the drawings. When assigning reference numerals to components in each drawing, the same numerals may be assigned to the same components even if they are shown in different drawings. In addition, when describing the present invention, if it is determined that a detailed description of related known configurations or functions may obscure the gist of the present invention, the detailed description may be omitted.
[0018] <Secondary battery> The present invention relates to secondary batteries, and more particularly to lithium secondary batteries.
[0019] Hereinafter, a secondary battery according to an embodiment of the present invention will be described with reference to Figures 1 to 3. Specifically, Figure 1 is a schematic side view for illustrating a secondary battery according to an embodiment of the present invention, Figure 2 is a schematic side view for illustrating an electrode assembly included in the secondary battery according to an embodiment of the present invention, and Figure 3 is a schematic side view for illustrating a separator included in the secondary battery according to an embodiment of the present invention.
[0020] 1 to 3, a secondary battery 10 according to an embodiment of the present invention includes an electrode assembly 100, a gel polymer electrolyte 200, and a battery case 300 that accommodates the electrode assembly 100 and the gel polymer electrolyte 200. The electrode assembly 100 includes a plurality of electrodes 110, 120 and a plurality of separators 130. The electrodes 110, 120 are stacked vertically, and each of the separators 130 is interposed between the stacked electrodes 110, 120. The separator 130 includes a porous substrate 1310 and ceramic coating layers 132a, 132b disposed on both sides of the porous substrate 131. The ceramic coating layers 132a, 132b include 92% by weight or more and less than 100% by weight of inorganic particles and more than 0% by weight and 8% by weight or less of a binder.
[0021] electrode assembly 100 For ease of explanation, FIG. 1 shows a simplified view of the electrode assembly, and FIG. 2 shows a more detailed structure of the electrode assembly 100. As shown in FIG.
[0022] The electrode assembly 100 includes a plurality of electrodes 110, 120 stacked in a vertical direction P. The number of the electrodes 110, 120 may be two or more. In this specification, the term "vertical direction" may refer to a vertical direction based on the ground and is intended to describe the stacking direction of the electrodes, and is not intended to limit the angle of the stacking direction.
[0023] The electrodes 110, 120 may include a first electrode 110 and a second electrode 120. As shown in FIG. 3, the first electrode 110 and the second electrode 120 may be alternately stacked. The electrodes 110, 120 may be alternately stacked with a plurality of separators 130 sandwiched between them. The first electrode 110 may be a positive electrode, and the second electrode 120 may be a negative electrode. Or, the first electrode 110 may be a negative electrode, and the second electrode 120 may be a positive electrode. The first electrode and the second electrode may each be one or more, specifically, two or more.
[0024] The first electrode 110 and the second electrode 120 may have a structure in which an active material slurry is applied to a current collector. The first electrode 110 and the second electrode 120 may have a structure formed by applying the active material slurry to both sides of a current collector, drying, and rolling. The active material slurry may be formed by stirring a granular active material, a conductive material, a binder, and the like in a solvent. The first electrode 110 and the second electrode 120 may use, without limitation, an active material, a conductive material, a binder, and the like used for a positive electrode or a negative electrode in the art.
[0025] The current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity. Specifically, the current collector can include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, and aluminum-cadmium alloy. For example, when the electrodes 110 and 120 are positive electrodes, the current collector used for the electrodes 110 and 120 can include aluminum, and when the electrodes 110 and 120 are negative electrodes, the current collector used for the electrodes 110 and 120 can include copper.
[0026] The current collector can be used in various forms such as a film, a sheet, a foil, a net, a mesh, a porous body, a foam, a nonwoven fabric, etc. The current collector can include a polymer layer and a metal layer disposed on both sides of the polymer layer, and the metal layer can include at least one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, and an aluminum-cadmium alloy.
[0027] Specifically, when the electrodes 110 and 120 are negative electrodes, the negative electrode active material contained therein may be, for example, a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), SnO 2 , vanadium oxide, lithium vanadium oxide, or other metal oxide capable of doping and dedoping lithium; or a composite containing the metallic compound and a carbonaceous material, such as a Si-C composite or a Sn-C composite, or any one or a mixture of two or more of these may be used. Also, a thin film of metallic lithium may be used as the negative electrode active material. Also, the carbon material may be either low crystalline carbon or high crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0028] Specifically, when the electrodes 110 and 120 are positive electrodes, the positive electrode active material contained therein is not particularly limited, and for example, the positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be lithium cobalt oxide (LiCoO 2), lithium nickel oxide (LiNiO 2 ), or compounds substituted with one or more transition metals; LiFe 3 O 4 Lithium iron oxide, etc.; chemical formula Li 1+c1 Mn 2-c1 O 4 (0≦c1≦0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 Lithium manganese oxides such as lithium copper oxide (Li 2 CuO 2 );LiV 3 O 8 , V 2 O 5 , Cu 2 V 2 O 7 Vanadium oxides such as LiNi 1-c2 Mc 2 O 2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.3); Ni-site type lithium nickel oxide represented by the chemical formula LiMn 2-c3 Mc 3 O 2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≦c3≦0.1) or Li 2 Mn 3 MO 8 Lithium manganese composite oxide represented by the formula LiMn (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); 2 O 4 The positive electrode may be a metallic lithium (Li-metal) positive electrode.
[0029] Examples of binders contained in the electrodes include polyvinylidene fluoride polymer, polyvinyl alcohol, styrene butadiene rubber, polyethylene oxide, carboxyl methyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinylalcohol, cyanoethyl cellulose, and cyanoethyl sucrose. The binder polymer may be any one selected from the group consisting of sucrose, pullulan, polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinyl acetate copolymer, polyarylate, and low molecular weight compounds having a molecular weight of 10,000 g / mol or less, or a mixture of two or more of these.
[0030] The conductive material contained in the electrode is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0031] An example of the thickener contained in the electrode is carboxymethyl cellulose (CMC).
[0032] 2, there may be a plurality of separators 130. Also, each of the plurality of separators 130 may be interposed between the electrodes 110 and 120.
[0033] As shown in FIG. 3, the separator 130 includes a porous substrate 131 and ceramic coating layers 132a, 132b disposed on both sides of the porous substrate.
[0034] The porous substrate 131 is not particularly limited as long as it is normally used as a separator for a secondary battery. Specifically, the porous substrate 131 is preferably one that has low resistance to ion migration of an electrolyte and has excellent electrolyte moisture absorption ability. More specifically, the porous substrate 131 may contain at least one selected from the group consisting of polyolefin resins such as polyethylene, polypropylene, polybutylene, and polypentene; fluorine resins such as polyvinylidene fluoride and polytetrafluoroethylene; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyacrylonitrile resins; and cellulose resins, and may be a porous film or nonwoven fabric containing one or more of these, or a copolymer or mixture thereof, or a laminate structure of two or more layers thereof. The porous substrate 131 may be a porous film, nonwoven fabric, or a laminate structure of two or more layers thereof containing the polyolefin resin.
[0035] The size and porosity of the pores present in the porous substrate 131 are not particularly limited. Specifically, the porous substrate 131 may be a porous substrate containing pores having an average pore diameter of 0.01 μm to 1 μm, specifically 20 nm to 60 nm, with a porosity of 10 vol% to 90 vol%, specifically 30 vol% to 60 vol%, in which case it is preferable in terms of improving the mechanical strength of the porous substrate 131 and allowing ionic substances to move more smoothly between the positive and negative electrodes. The average pore diameter and porosity may be measured by analysis using a focused ion beam (FIB), a gas adsorption method, or a mercury intrusion method.
[0036] The thickness of the porous substrate 131 is not particularly limited, but may be, in consideration of appropriate mechanical strength as a separator and ease of movement of ionic substances, specifically, 1 μm to 100 μm, more specifically, 2 μm to 15 μm.
[0037] The ceramic coating layers 132 a and 132 b are disposed on both sides of the porous substrate 131 .
[0038] The ceramic coating layers 132a and 132b include inorganic particles and a binder. More specifically, the ceramic coating layers may consist of only the inorganic particles and the binder.
[0039] The inorganic particles may be introduced to prevent thermal shrinkage of the porous substrate at high temperatures and the resulting short circuit between the positive and negative electrodes, and the inorganic particles may serve as a kind of spacer that can maintain the physical shape of the porous substrate and minimize thermal shrinkage.
[0040] The inorganic particles are preferably those having a voltage range within the operating voltage range of the battery (e.g., Li / Li + As long as it is electrochemically stable at a voltage of 0 V to 5 V relative to the reference voltage and does not cause an oxidation and / or reduction reaction, i.e., an electrochemical reaction, any inorganic particles can be used without particular limitation. 3 PO 4 ); Lithium titanium phosphate (Li x Ti y (PO 4 ) 3 , 0 <x<2、0<y<3);リチウムアルミニウムチタンホスフェート(Li x Al y Ti z (PO 4 ) 3 , 0 <x<2、0<y<1、0<z<3)、14Li 2 O-9Al 2 O 3 -38TiO 2 -39P 2 O 5 Like (LiAlTiP) x O y Glass (0 <x<4、0<y<13);リチウムランタンチタネート(Li x La y TiO 3 , 0 <x<2、0<y<3);Li 3.25 Ge 0.25 P 0.75 S 4Lithium germanium thiophosphates (Li x Ge y P z S w , 0 <x<4、0<y<1、0<z<1、0<w<5);Li 3 Lithium nitride such as N (Li x N y , 0 <x<4、0<y<2);Li 3 PO 4 -Li 2 S-SiS 2 and other SiS 2 Li-based glass x S y S z , 0 <x<3、0<y<2、0<z<4);LiI-Li 2 SP 2 S 5 P such as 2 S 5 Li-based glass x P y S z , 0 <x<3、0<y<3、0<z<7);Al 2 O 3 ;AlOOH;BaTiO 3 ;BaSO 4 ;MgO;CaO;CeO 2 ;NiO;SiO 2 ;SnO 2 ;SrTiO 3 ;TiO 2 ;Y 2 O 3 ;ZnO;ZrO 2 ;Pb(Zr,Ti)O 3 (PZT); Pb 1-x La x Zr 1-y Ti y O 3 (PLZT);PB(Mg 3 Nb 2 / 3 )O 3 -PbTiO 3 (PMN-PT); Hafnia (HfO 2 ); It can be a mixture of two or more of these. Specifically, the inorganic particles are Al 2 O 3 ;AlOOH;BaTiO 3;BaSO 4 ;MgO;CaO;CeO 2 ;NiO;SiO 2 ;SnO 2 ;SrTiO 3 ;TiO 2 ;Y 2 O 3 ;ZnO;ZrO 2 ;Pb(Zr,Ti)O 3 (PZT); Pb 1-x La x Zr 1-y Ti y O 3 (PLZT);PB(Mg 3 Nb 2 / 3 )O 3 -PbTiO 3 (PMN-PT); Hafnia (HfO 2 ); and mixtures of two or more of these, more specifically, Al 2 O 3 ;AlOOH;BaTiO 3 ;BaSO 4 and MgO.
[0041] The average particle size of the inorganic particles (D 50 ) can be 0.1 μm to 1 μm, specifically 0.2 μm to 0.7 μm.
[0042] The inorganic particles are included in the ceramic coating layers 132a and 132b in an amount of 92% by weight or more and less than 100% by weight. The content of the inorganic particles should be considered in relation to the content of the binder described below, and can be adjusted to prevent a decrease in thermal stability due to thermal contraction of the porous substrate and to prevent an increase in resistance due to an excessive amount of binder. Specifically, the inorganic particles can be included in the ceramic coating layers in an amount of 93% by weight to 98% by weight.
[0043] The binder may be included in the ceramic coating layers 132a and 132b to bind inorganic particles and to bind the separator and electrodes.
[0044] Here, the binder is contained in the ceramic coating layer in an amount of more than 0 wt % and less than 8 wt %. If the binder is contained in an amount of more than 8 wt %, the binder is excessively contained in the ceramic coating layer, which may cause an increase in the resistance of the secondary battery. On the other hand, if the binder is contained in the above range, there is a risk of a decrease in the cell rigidity of the secondary battery due to a decrease in the adhesive strength between the electrode and the separator. However, as described below, the present invention uses a combination of a separator having the above characteristics and a gel polymer electrolyte, and therefore can simultaneously achieve an improvement in the resistance of the secondary battery, as well as an improvement in cell rigidity and mechanical durability.
[0045] Specifically, the binder may be included in the ceramic coating layer in an amount of 2 wt % to 7 wt %, and when the amount is within this range, the binding force of the inorganic particles can be maximized and an increase in the resistance of the secondary battery can be prevented.
[0046] The binder may contain a fluorine group (-F), an acrylate group (CH 2 =CHCOO-), methacrylate group (CH 2 =C(CH 3 )COO-), vinyl acetate group (-CH 2 The binder is a hydrophobic binder containing one or more hydrophobic functional groups such as hydroxyl groups (-OH), carboxyl groups (-COOH), maleic anhydride groups (-COOOC-), sulfonic acid groups (-SO 3The hydrophobic binder may be a hydrophilic binder containing one or more polar groups such as a fluorine atom (H) or an isocyanate group (-NCO-), and any one or a mixture of two or more of these may be used. More specifically, the hydrophobic binder may be polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyacrylonitrile, polyvinylacetate, ethylene-vinylacetate copolymer, polyimide, polyethylene oxide, etc. In addition, the hydrophilic binder may be cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, carboxyl methyl cellulose, polyvinyl alcohol, polyacrylic acid, polymaleic anhydride, polyvinylpyrrolidone, or the like.
[0047] Specifically, the binder may be an acrylic binder. The acrylic binder allows the inorganic particles to be well dispersed during the preparation of the ceramic coating layer, thereby preventing the ceramic coating layer from being separated into layers, with the binder in the upper layer and the inorganic particles in the lower layer. Such layer separation results in impeding ion migration in the negative and positive electrodes, causing an increase in resistance. Therefore, when an acrylic binder is used as the binder, the resistance reduction effect aimed at by the present invention can be exhibited at a more excellent level.
[0048] The acrylic binder may include at least one selected from the group consisting of a copolymer of ethylhexyl acrylate and methyl methacrylate; polymethylmethacrylate; polyethylhexylacrylate; polybutylacrylate; polyacrylonitrile; and a copolymer of butyl acrylate and methyl methacrylate.
[0049] The ceramic coating layer may contain inorganic particles and a binder in a weight ratio of 92:8 or more and less than 100:0, specifically 93:7 to 98:2.
[0050] The ceramic coating layers 132a and 132b may have a thickness of 0.1 μm to 10 μm, specifically 0.5 μm to 5 μm, and more specifically 1.0 μm to 2.5 μm. Since the ceramic coating layers 132a and 132b contain the binder in the above-mentioned small content, a separator with a thin thickness can be realized, and the energy density of the secondary battery can be further improved and low resistance can be realized. The thickness of the ceramic coating layer may refer to the thickness of one ceramic coating layer formed on one surface of the porous substrate.
[0051] The ceramic coating layers 132a and 132b may be prepared by applying a ceramic coating layer forming composition, in which inorganic particles and a binder are dispersed in a solvent, to the porous substrate and drying the composition. The method of applying the ceramic coating layer forming composition is not particularly limited, and may be dip coating, die coating, roll coating, comma coating, gravure coating, etc., and more specifically, gravure coating may be used. The drying method after application of the ceramic coating layer forming composition may be natural drying, heat drying, hot air drying, etc.
[0052] The thickness of the separator 130 may be 1 μm to 20 μm, specifically 5 μm to 14 μm. According to the present invention, since the binder content in the ceramic coating layer is reduced, a separator with a thin thickness can be realized, and thus the energy density of the secondary battery can be further improved and low resistance can be achieved.
[0053] As shown in FIG. 1, the secondary battery may further include a plurality of electrode tabs 400, 500 connected to the electrode assembly. Specifically, the plurality of electrode tabs 400, 500 may be connected to the electrodes 110, 120 of the electrode assembly 100, more specifically, to the first electrode 110 and the second electrode 120, respectively, and may protrude to the outside of the battery case 300 to become a path through which electrons can move. In addition, in FIG. 1, the two electrode tabs 400, 500 are illustrated as being arranged in different directions with respect to the electrode assembly 100, but are not limited thereto, and may protrude in parallel in the same direction from one side of the electrode assembly 100. The plurality of electrode tabs 400, 500 may be positive electrode tabs and negative electrode tabs, and may be connected to the positive electrode and the negative electrode, respectively.
[0054] Gel Polymer Electrolyte 200 The gel polymer electrolyte 200 is injected or housed in a battery case 300, which will be described later. The gel polymer electrolyte 200 may be impregnated into the electrode assembly 100, hardened, and disposed inside and outside the electrode assembly.
[0055] The gel polymer electrolyte 200 is a gelled electrolyte with no fluidity, and therefore can improve the cell rigidity of the secondary battery. In particular, the present invention can realize a secondary battery with reduced resistance and improved cell rigidity by using the gel polymer electrolyte together with the above-mentioned separator. On the other hand, when the above-mentioned separator and liquid electrolyte are used, the cell rigidity is excessively reduced, which may lead to cell deflection, separator misalignment, and other problems that may lead to reduced processability and product defects, reduced safety, and the possibility of secondary battery explosion.
[0056] The gel polymer electrolyte 200 may be a cured product of a gel polymer electrolyte composition including a lithium salt, a polymerization initiator, and an oligomer compound. When the gel polymer electrolyte composition is cured, the oligomer compound is crosslinked and cured to form an electrolyte (gel polymer electrolyte) solidified in a gel form. Specifically, the gel polymer electrolyte 200 may include the cured product of the oligomer compound and a lithium salt.
[0057] The lithium salt can be used for the purpose of providing lithium ions to a secondary battery.
[0058] The lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in a secondary battery. Specifically, the lithium salt is LiPF 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAl0 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F9 SO 3 , LiN(C 2 F 5 SO 3 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 .LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 M to 5.0 M, preferably 0.1 M to 3.0 M. When the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance, allowing lithium ions to migrate effectively.
[0059] The polymerization initiator may be used for the purpose of polymerizing oligomeric compounds to form a polymer network connected in a three-dimensional structure.
[0060] The polymerization initiator may be a photopolymerization initiator or a thermal polymerization initiator depending on the polymerization method.
[0061] Specifically, the photopolymerization initiator may be, for example, 2-hydroxy-2-methylpropiophenone (HMPP), 1-hydroxy-cyclohexylphenyl-ketone, benzophenone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, oxy-phenylacetic acid 2-[2-iodo-2-phenyl-acetoxy-ethoxy]-ethyl ester, oxy-phenyl-acetic acid 2-[2-hydroxyethoxy]-ethyl ester, alpha-dimethoxy-alpha-phenylacetophenone, 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholinyl)phenyl ]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(eta5-2,4-cyclopentadiene-1-yl), bis[2,6-difluoro-3-(1H-pyrrol-1-yl)phenyl]titanium, 4-isobutylphenyl-4'-methylphenyliodonium, hexafluorophosphate, and methylbenzoylformate.
[0062] Representative examples of the thermal polymerization initiator include at least one compound selected from the group consisting of benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, t-butyl peroxy-2-ethyl-hexanoate, cumyl hydroperoxide, and hydrogen peroxide, 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), 2,2'-azobis(isobutyronitrile) (AIBN), and 2,2'-azobisdimethyl-valeronitrile (AMVN).
[0063] The polymerization initiator can be decomposed by heat at 30°C to 100°C in the secondary battery or by light such as UV at room temperature (5°C to 30°C) to form radicals, and cross-linking bonds can be formed by free radical polymerization to polymerize the oligomer.
[0064] Meanwhile, the polymerization initiator may be used in an amount of 0.001 to 10 parts by weight, preferably 0.0015 to 1 part by weight, more preferably 0.002 to 0.7 parts by weight, based on 100 parts by weight of the oligomer compound. When the amount of the polymerization initiator used is within the above range, the amount of unreacted polymerization initiator that may adversely affect battery performance can be minimized. In addition, when the polymerization initiator is used within the above range, gelation of the electrolyte composition can be appropriately performed.
[0065] The oligomer compound may include at least one selected from the group consisting of polyether-based oligomers, polycarbonate-based oligomers, acrylate-based oligomers, polysiloxane-based oligomers, phosphagene-based oligomers, polyethylene-based oligomers, urethane-based oligomers, epoxy-based oligomers, fluorine-based oligomers, polyethylene oxide, polyester sulfide, polyvinyl alcohol, and polyvinylidene fluoride, specifically at least one selected from fluorine-based oligomers, polycarbonate-based oligomers, and polysiloxane-based oligomers.
[0066] For example, the fluorine-based oligomer may specifically include a unit derived from a fluorine-based monomer. The fluorine-based oligomer has an advantage that the fluorine-based functional group contained therein suppresses the generation of oxygen radicals caused by the decomposition of the positive electrode active material, thereby further improving battery stability and having excellent flame retardancy. More specifically, the fluorine-based oligomer may include at least one selected from tetrafluoroethylene (TFE)-vinyl acetate copolymer, (allyl 1,1,2,2-tetrafluoroethyl ether)-(2,2,2-trifluoroethyl acrylate) copolymer, tetrafluoroethylene-(2-vinyl-1,3-dioxolane) copolymer, and tetrafluoroethylene-vinyl methacrylate copolymer.
[0067] In addition, the polycarbonate oligomer has an affinity with the positive electrode, a structure similar to that of an organic electrolyte, and an advantage in that it has excellent ion conductivity or ion dissociation degree. The polycarbonate oligomer may be a polycarbonate having a weight average molecular weight of 1,000 g / mol to 50,000 g / mol, specifically 4,500 g / mol to 30,000 g / mol, more specifically 10,000 g / mol to 25,000 g / mol.
[0068] In addition, the polysiloxane oligomer can function as a scavenger for gases (such as HF) generated by side reactions of the electrolyte, thereby improving high-temperature storage characteristics.
[0069] The weight average molecular weight of the oligomer compound can be from 1,000 g / mol to 50,000 g / mol, specifically from 4,500 g / mol to 30,000 g / mol.
[0070] The oligomer compound may be included in the gel polymer electrolyte composition in an amount of 1 wt % to 20 wt %, specifically 3 wt % to 10 wt %, and when included in the above range, the effect of improving the cell rigidity of the secondary battery can be excellent, and the ion conductivity and lithium ion mobility of the gel polymer electrolyte can be excellent.
[0071] The gel polymer electrolyte composition may further include a solvent in addition to the lithium salt, the polymerization initiator, and the oligomer compound. The solvent may be used to dissolve or disperse the lithium salt, the polymerization initiator, and the oligomer compound.
[0072] The solvent is one that is commonly used in secondary batteries, and for example, ethers, esters (acetates, propionates), amides, linear or cyclic carbonates, nitriles (acetonitrile, SN, etc.), etc., can be used alone or in combination of two or more.
[0073] Among them, typically, carbonate-based solvents containing a carbonate compound such as a cyclic carbonate, a linear carbonate, or a mixture thereof can be used as the first solvent.
[0074] Specific examples of the cyclic carbonate compound include a single compound or a mixture of at least two selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, and halides thereof. Specific examples of the linear carbonate compound include a compound or a mixture of at least two selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC), but are not limited thereto.
[0075] In particular, among the carbonate-based solvents, propylene carbonate and ethylene carbonate, which are cyclic carbonates, are preferably used since they are high-viscosity organic solvents with high dielectric constants and can easily dissociate lithium salts in the electrolyte. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as ethyl methyl carbonate, diethyl carbonate, or dimethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be obtained, and therefore the mixture can be more preferably used.
[0076] Among the solvents, the ester may be a single compound or a mixture of at least two compounds selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, α-valerolactone, and ε-caprolactone, but is not limited thereto.
[0077] Here, the gel polymer electrolyte composition may be cured at a temperature of 50° C. to 100° C. for 0.5 to 48 hours, and preferably at a temperature of 60° C. to 80° C. for 0.5 to 24 hours.
[0078] Battery case 300 The battery case 300 may be provided for the purpose of housing the electrode assembly 100 and the gel polymer electrolyte 200 .
[0079] The battery case 300 may be a pouch-shaped case made of a flexible material, for example, an aluminum pouch battery case.
[0080] When the battery case 300 is an aluminum pouch battery case, the battery case 300 can be formed of a pouch film in which, for example, a polypropylene layer (PP layer), an aluminum layer, and a polyethylene terephthalate layer (PET layer) are laminated in this order from the inside.
[0081] The battery case 300 may include a cup portion that is a receiving space for receiving the electrode assembly.
[0082] The battery case 300 may include a cover 310, and after the electrode assembly is housed and the gel polymer electrolyte composition is hardened and gelled, the battery case 300 may be sealed with the cover to manufacture a sealed secondary battery.
[0083] Hereinafter, a secondary battery according to another embodiment of the present invention will be described with reference to Fig. 4 and Fig. 5. Fig. 4 is a schematic side view illustrating an electrode assembly included in a secondary battery according to another embodiment of the present invention. Fig. 5 is a schematic plan view of any one of electrodes 110, 120 or separator 130 included in the secondary battery according to another embodiment of the present invention.
[0084] Referring to FIG. 4, the secondary battery according to another embodiment of the present invention may be the same as the secondary battery described above, except that the electrode assembly 100 is manufactured by applying an adhesive to the surface of at least one of the electrodes 110, 120 and the separator 130, and the electrodes 110, 120 and the separator 130 are bonded to each other, and the gel polymer electrolyte 200 and the electrode assembly 100 are housed in the battery case 300, whereby the adhesive is removed and adhesive application marks 140 remain on the surface of at least one of the electrodes 110, 120 and the separator 130.
[0085] The adhesive may be used to introduce adhesion for the electrodes 110, 120 and the separator 130. Specifically, the adhesive may be introduced to fix the alignment position of the electrodes and the separator in the process of laminating, assembling, and stacking them in the manufacturing process of the secondary battery. As described above, the separator 130 according to the present invention has a reduced binder content, and the adhesive may not be sufficient between the electrodes and the separator during the manufacturing process of the secondary battery, so the adhesive compensates for this problem, easily bonds the electrodes and the separator, and prevents the separator from shifting during the manufacturing process of the electrode assembly, thereby improving the efficiency and quality of the process.
[0086] The adhesive is used to manufacture an electrode assembly by adhering an electrode and a separator, and may be removed after the electrode assembly is accommodated in a battery case and the gel polymer electrolyte is accommodated therein. Specifically, the adhesive may be dissolved and removed by a solvent in a gel polymer electrolyte composition for forming the gel polymer electrolyte. In a secondary battery according to another embodiment of the present invention, the adhesive is used to easily adhere an electrode and a separator without increasing the amount of binder in the separator, and also to prevent an increase in the thickness of the separator due to an increase in the amount of binder, thereby further improving the energy density of the secondary battery.
[0087] The adhesive may be applied in a plurality of patterns spaced apart from one another. Specifically, the adhesive may be applied on a surface of at least one of the electrodes and the separator in a plurality of patterns spaced apart from one another. Specifically, the adhesive may be applied on a surface of at least one of the electrodes and the separator in a plurality of dots spaced apart from one another.
[0088] 4 and 5, the adhesive is removed by housing the gel polymer electrolyte in a battery case or by injecting the gel polymer electrolyte composition into a battery case, and adhesive application marks 140 may remain on the surfaces of at least one of the electrodes 110, 120 and the separator 130. Specifically, when the gel polymer electrolyte composition is injected into a battery case housing the electrode assembly, the adhesive may be dissolved and removed by a solvent in the gel polymer electrolyte composition, leaving behind adhesive application marks.
[0089] The application area of the adhesive may be more than 0% and 1% or less, specifically 0.0001% to 0.05%, of the surface area where the separator and the electrode contact each other. When the application area is within this range, the electrode and the separator can be bonded with sufficient adhesive strength, and the adhesive can be prevented from being applied in excess and remaining in the solvent without being dissolved, which causes an increase in resistance, which is preferable.
[0090] The adhesive may be an acrylate adhesive. By using the acrylate adhesive, the adhesive can be easily dissolved and removed. A detailed description of the adhesive will be given later.
[0091] The position of the adhesive application marks 140 is not particularly limited, and for example, the adhesive application marks 140 may be disposed at the same position between the electrodes 110, 120 and the separator 130. For example, as shown in FIG. 4, the adhesive application marks 140 located between the lower part of the first electrode 110 and the separator 130 and the adhesive application marks 140 located between the upper part of the first electrode 110 and the separator 130 may be disposed on the same vertical line based on the bottom surface, and the intervals at which the adhesive application marks 140 are disposed may be the same. This can be similarly explained in the case of the adhesive application marks 140 located between the second electrode 120 and the separator 130. When the adhesive application marks are disposed at the same position between the electrodes 110, 120 and the separator 130, there is an advantage that the adhesive application process is simplified and the process time and efficiency are increased.
[0092] As shown in Fig. 4 and Fig. 5, the adhesive application mark 140 is formed by applying and removing the adhesive, and may be present between the surfaces of the electrodes 110, 120 and the separator 130 in contact with each other, and may remain on the surface of at least one of the electrodes 110, 120 and the separator 130. In the case of an electrode assembly including the separator described above, there is a risk of quality defects and reduced process efficiency due to misalignment between the electrodes and the separator when the separator and the electrodes are stacked in the manufacturing process. However, according to the present invention, the adhesive is applied to bond the electrodes and the separator, so that the above-mentioned misalignment phenomenon of the electrodes and / or the separator can be significantly prevented, and a secondary battery with improved quality can be manufactured. Such application of the adhesive and the arrangement of the adhesive application mark are particularly preferable in terms of complementing the adhesive force of the separator in the present invention, which contains a low content of binder.
[0093] Hereinafter, with reference to FIG. 6, a secondary battery according to still another embodiment of the present invention will be described.
[0094] A secondary battery according to yet another embodiment of the present invention may be the same as the secondary battery described with reference to Figures 4 and 5, except that adhesive application marks 141, 142 are disposed between the electrodes 110, 120 and the separator 130, and the adhesive application marks 141, 142 disposed in adjacent layers may be disposed in a cross-shaped manner.
[0095] 6, a first adhesive application mark 141 located between the lower portion of the first electrode 110 and the separator 130 and a second adhesive application mark 142 located between the upper portion of the first electrode 110 and the separator 130 may be disposed to cross each other. Here, the first adhesive application mark 141 and the second adhesive application mark 142 may cross each other only in position, and the intervals between them may be the same. This can be similarly explained in the case of the adhesive application marks 141, 142 located between the second electrode 120 and the separator 130.
[0096] In the case of such a cross-arrangement of adhesive application marks, it is preferable in that the risk of an increase in cell thickness due to application of adhesive can be minimized and the adhesive can be dissolved more smoothly.
[0097] <Secondary battery manufacturing method> The present invention also provides a method for producing a secondary battery, which may be the method for producing the secondary battery described above.
[0098] Specifically, the method for manufacturing the secondary battery includes the steps of housing an electrode assembly in the battery case, injecting a gel polymer electrolyte composition into the battery case, hardening the gel polymer electrolyte, and sealing the battery case, the electrode assembly including a plurality of electrodes and a plurality of separators, the plurality of electrodes being stacked vertically, each of the plurality of separators being interposed between the stacked electrodes, the separator including a porous substrate and a ceramic coating layer disposed on both sides of the porous substrate, the ceramic coating layer including 92 wt % or more and less than 100 wt % of inorganic particles and more than 0 wt % and 8 wt % or less of a binder.
[0099] The secondary battery may be manufactured by a method including the steps of: housing an electrode assembly in a battery case, injecting a gel polymer electrolyte composition into the battery case, curing the gel polymer electrolyte composition, and sealing the battery case. After sealing the battery case, activation, degassing, resealing, and the like, which are known in the art, may be further performed.
[0100] The electrode assembly, electrodes, separator, battery case, gel polymer electrolyte composition, etc. are the same as those described above.
[0101] In the present invention, the electrode assembly may be manufactured by applying an adhesive to at least one surface of the electrode and the separator, thereby adhering the electrode and the separator to each other.
[0102] Exemplarily, the electrode assembly may be manufactured by a method including the following steps (a) to (c) as illustrated in FIGS.
[0103] (a) applying an adhesive 140a to at least one of one surface of the first electrode 110 and one surface of the first separator 130a, and adhering the first electrode 110 and the first separator 130a by the applied adhesive 140a; (b) applying an adhesive 140a to at least one of the other surface of the first electrode 110 and one surface of the second separator 130b, and adhering the first electrode 110 and the second separator 130b by the applied adhesive 140a; and (c) applying an adhesive 140a to at least one of the other surface of the second separator 130b and the one surface of the second electrode 120, and bonding the second separator 130b and the second electrode 120 together with the applied adhesive 140a.
[0104] Specifically, referring to FIG. 7, adhesive 140a may be applied to one side of first separator 130a first. The application of adhesive may be performed by a nozzle 600 containing adhesive. Referring to FIG. 8, the first electrode 110 is then disposed on one side of first separator 130a to which adhesive 140a has been applied, and bonded thereto. Although FIGS. 7 and 8 illustrate that adhesive 140a is applied to first separator 130a, the present invention is not limited thereto, and adhesive may be applied to one side of first electrode 110 beforehand, and then bonded to first separator 130a, or adhesive may be applied to both one side of first electrode 110 and one side of first separator 130a, and then first electrode 110 and first separator 130a may be bonded to each other (step (a)).
[0105] Referring to FIG. 9, an adhesive 140a may be applied to the other side of the first electrode 110. Specifically, the other side of the first electrode 110 may refer to the opposite side of the surface where the first electrode 110 and the first separator 130a are in contact. FIG. 9 illustrates the adhesive 140a being applied to the other side of the first electrode 110, but the present invention is not limited thereto. The adhesive may be applied in advance to the second separator 130b to be attached to the first electrode 110, or the first electrode 110 and the second separator 130b may be attached to each other after the adhesive is applied to both the first electrode 110 and the second separator 130b. Referring to FIG. 10, the second separator 130b is then disposed and attached to the other side of the first electrode 110 (step (b)).
[0106] Referring to FIG. 11, next, adhesive 140a is applied to the other surface of the second separator 130b (the surface of the second separator 130b opposite to the surface where the first electrode 110 and the second separator 130b are in contact), and then the second electrode 120 is positioned and adhered (step (c)).
[0107] The electrode assembly may be manufactured by stacking one or more, specifically two or more, basic units each having a sequentially stacked structure of the first electrode, the first separator, the second electrode and the second separator manufactured by the method including steps (a) to (c). The basic units may be stacked by adhering them to each other with an adhesive.
[0108] In the past, there was a possibility of process defects such as distortion or misalignment during the lamination process of electrodes and separators. However, according to the present invention, an adhesive is applied when each electrode and separator is laminated, which improves the adhesive strength of the electrodes and separators and enables accurate alignment of the electrodes and separators, making it possible to manufacture secondary batteries with improved process efficiency and quality.
[0109] The adhesive may be applied in a plurality of patterns spaced apart from each other. Specifically, the adhesive may be applied in a plurality of patterns spaced apart from each other on at least one surface of the first electrode and the separator, and at least one surface of the second electrode and the separator. Specifically, the adhesive may be applied in a plurality of dots spaced apart from each other on at least one surface of the first electrode and the separator, and at least one surface of the second electrode and the separator.
[0110] The adhesive may be dissolved and removed by the gel polymer electrolyte composition injected into the battery case. The gel polymer electrolyte composition may further include a solvent in addition to the lithium salt, polymerization initiator, and oligomer compound, and the adhesive may be dissolved and removed by the solvent included in the gel polymer electrolyte composition.
[0111] The adhesive may be removed by housing the gel polymer electrolyte in a battery case or by injecting the gel polymer electrolyte composition into the battery case, and a trace of the adhesive application may remain on the surface of at least one of the separator and the electrode. Specifically, when the gel polymer electrolyte composition is injected into a battery case housing the electrode assembly, the adhesive may be dissolved and removed by a solvent in the gel polymer electrolyte composition, leaving a trace of the adhesive application.
[0112] The adhesive may be dissolved or removed more smoothly by applying pressure in the activation and degassing processes generally involved in the secondary battery manufacturing process. The activation is a process of forming a solid electrolyte interface layer (SEI layer) on the surface of the electrode plate of the electrode assembly in the initial secondary battery by a charging process to charge the electrode plate, thereby enabling the secondary battery to supply power, and may be performed at a temperature of, for example, 45° C. or higher, specifically, 50° C. to 70° C. The degassing process is a process of discharging gas generated during the activation process to the outside, and the degassing process may include a process of pressurizing the secondary battery using a jig or the like. The adhesive may be dissolved or removed more smoothly by such an increase in temperature and pressure.
[0113] The adhesive may be an acrylate adhesive, and by using the acrylate adhesive, the adhesive can be easily dissolved and removed.
[0114] Specifically, the acrylate adhesive may include a copolymer including repeat units derived from at least one monomer selected from the group consisting of methyl methacrylate (MMA), 2-ethylhexyl acrylate (2-EHA), and 2-hydroxyethyl acrylate (2-HEA).
[0115] The weight average molecular weight (Mw) of the copolymer may be 120,000 g / mol to 140,000 g / mol. The molecular weight of the copolymer can be measured by a conventional method well known in the art. For example, the molecular weight can be measured by a terminal group quantitative analysis of functional groups at the molecular chain end to determine the molecular weight, a generalized method using physical properties such as osmotic pressure, vapor pressure depression, boiling point elevation, and freezing point depression (separator permeation method, vapor pressure osmometry, etc.), a light scattering method using light scattering, an ultracentrifugation method in which a polymer solution is centrifuged and then the sedimentation velocity or concentration distribution is analyzed to measure the molecular weight, a viscosimetry using the viscosity of the polymer solution, gel permeation chromatography (GPC) using high performance liquid chromatography (HPLC), etc. can be used.
[0116] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings, in which: FIG. 1 is a block diagram of a semiconductor device according to an embodiment of the present invention;
[0117] Examples and Comparative Examples Example 1 1. Manufacturing of separators Al as inorganic particles 2 O 3 (Average particle size (D 50 A ceramic coating layer-forming composition was prepared by adding 100% cellulose acetate (0.5 μm) and an acrylic binder to a solvent, water, in a weight ratio of 96:4. As the acrylic binder, a mixture of TRD 202A manufactured by JSR and AP-0821 manufactured by APEC was used.
[0118] The composition for forming a ceramic coating layer was applied by gravure coating to both sides of a polyethylene porous substrate (thickness: 9 μm, average pore size: 0.05 μm, porosity: 45% by volume) and dried to form a ceramic coating layer (thickness of one layer: 1.5 μm), thereby producing a separator (thickness: 12 μm = 1.5 μm + 9 μm + 1.5 μm).
[0119] 2. Manufacturing the electrode assembly A plurality of the separators manufactured as described above were prepared, and a plurality of positive electrodes and negative electrodes were prepared.
[0120] The adhesive was applied onto the separator in a pattern of spaced apart dots using a nozzle. The adhesive application area (5.8875 mm 2 ) is the surface area where the separator and the positive electrode come into contact (24,889 mm 2 The adhesive was an acrylate adhesive, which was a copolymer containing repeat units derived from methyl methacrylate (MMA), 2-ethylhexyl acrylate (2-EHA) and 2-hydroxyethyl acrylate (2-HEA) in a weight ratio of 40:30:30.
[0121] Next, the positive electrode was placed and adhered to the adhesive-coated surface of the separator.
[0122] Next, an adhesive was applied to the surface of the positive electrode opposite to the surface where the positive electrode and the separator were in contact with each other using a nozzle in a pattern of a plurality of dots spaced apart from each other. Next, another separator was placed on the positive electrode and bonded thereto.
[0123] Next, an adhesive was applied to the other separator with a nozzle in a pattern of a plurality of spaced dots, and the negative electrode was then positioned and adhered thereto.
[0124] The above process was repeated several times to prepare an electrode assembly in which 18 basic units each having a separator / positive electrode / separator / negative electrode stacked in sequence were stacked.
[0125] Here, in the case of the positive electrode, the positive electrode active material is Li[Ni 0.8 Co 0.1 Mn 0.1 ]O 2A positive electrode slurry was prepared by adding PVDF as a binder and carbon black as a conductive material in a weight ratio of 97.5:1.5:1.0 to N-methylpyrrolidone (NMP) as a solvent, and the positive electrode slurry was applied to both sides of an aluminum current collector as a positive electrode current collector, which was then dried and rolled to form a positive electrode active material layer.
[0126] In addition, in the case of the negative electrode, graphite as a negative electrode active material, styrene-butadiene rubber as a binder, carbon black as a conductive material, and carboxymethyl cellulose (CMC) as a thickener were added to water as a solvent in a weight ratio of 95.5:2.5:1.0:1.0 to prepare a negative electrode slurry, and the negative electrode slurry was applied to both sides of a copper current collector as a negative electrode current collector, which was then dried and rolled to form a negative electrode active material layer.
[0127] 3. Preparation of Gel Polymer Electrolyte Composition The gel polymer electrolyte composition is made of polycarbonate (weight average molecular weight Mw: 20,000) as an oligomer and LiPF as a lithium salt. 6 It was produced by mixing AIBN (Azobisisobutyronitrile) as a polymerization initiator in a solvent.
[0128] The solvent was a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7, the lithium salt was contained in the gel polymer electrolyte composition at a concentration of 1.0 M, the oligomer was contained in the gel polymer electrolyte composition at 5 wt %, and the polymerization initiator was contained in the gel polymer electrolyte composition at 0.6 parts by weight relative to 100 parts by weight of the oligomer.
[0129] 4. Secondary battery manufacturing A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly was housed in the housing space of the battery case.
[0130] Next, a gel polymer electrolyte composition was injected into the battery case containing the electrode assembly, and the battery case was vacuum sealed after the gel polymer electrolyte composition was injected.
[0131] The adhesive present in the electrode assembly was dissolved and removed by the solvent of the gel polymer electrolyte composition due to the injection of the gel polymer electrolyte composition. As described below, the adhesive was removed, but traces of the adhesive remained on the separator and electrodes.
[0132] Next, the gel polymer electrolyte composition injected into the battery case was cured by heat treatment at a temperature of 60° C. for 5 hours.
[0133] The battery case was then cooled, sealed and degassed to produce a secondary battery having a thickness of 0.8 cm.
[0134] Comparative Example 1 1. Manufacturing of separators Al as inorganic particles 2 O 3 (Average particle size (D 50 ):0.5 μm) and PVdF as a binder were added to acetone as a solvent in a weight ratio of 70:30 to prepare a composition for forming a ceramic coating layer.
[0135] The composition for forming a ceramic coating layer was applied to both sides of a polyethylene porous substrate (thickness: 9 μm, average pore size: 0.05 μm, porosity: vol%) by gravure coating, and then dried to form a ceramic coating layer (thickness of one layer: 3 μm), thereby producing a separator (thickness: 15 μm = 3 μm + 9 μm + 3 μm).
[0136] 2. Manufacturing the electrode assembly Unlike Example 1, no adhesive was applied, and a secondary battery was manufactured in the same manner as in Example 1, except that the separator manufactured as described above was used.
[0137] 3. Preparation of Liquid Electrolyte Composition The solvent used was a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:70, and lithium salt LiPF 6 was added at a concentration of 1.0 M to prepare a liquid electrolyte composition.
[0138] 4. Secondary battery manufacturing A pouch-type battery case made of aluminum was prepared as the battery case, and the electrode assembly manufactured as described above was placed in the storage space of the battery case.
[0139] Next, the liquid electrolyte composition prepared above was poured into the container, and the container was vacuum sealed.
[0140] The battery case was cooled, sealed and degassed to produce a secondary battery having a thickness of 0.8 cm.
[0141] Comparative Example 2 1. Manufacturing of separators The same separator as that produced in Comparative Example 1 was used.
[0142] 2. Manufacturing the electrode assembly The same electrode assembly as that manufactured in Comparative Example 1 was used.
[0143] 3. Preparation of Gel Polymer Electrolyte Composition The same gel polymer electrolyte composition as that prepared in Example 1 was used.
[0144] 4. Secondary battery manufacturing Except for using the separator and electrode assembly prepared above, a secondary battery was manufactured in the same manner as in Example 1. The thickness of the secondary battery was 0.8 cm.
[0145] Comparative Example 3 1. Manufacturing of separators The same separator as that produced in Example 1 was used.
[0146] 2. Manufacturing the electrode assembly The same electrode assembly as that manufactured in Example 1 was used.
[0147] 3. Preparation of Liquid Electrolyte Composition The same liquid electrolyte composition as that prepared in Comparative Example 1 was used.
[0148] 4. Secondary battery manufacturing Except for using the separator and electrode assembly prepared above, a secondary battery was manufactured in the same manner as in Comparative Example 1. The thickness of the secondary battery was 0.8 cm.
[0149] Experimental Example 1. Observation of adhesive marks on the separator surface In the secondary batteries of Example 1 and Comparative Example 1, the separator corresponding to the surface where the electrode and the separator were in contact was cut and the surface was observed. A photograph of the surface of the separator separated from the secondary battery of Example 1 is shown in Fig. 12, and a photograph of the surface of the separator separated from the secondary battery of Comparative Example 1 is shown in Fig. 13.
[0150] As shown in FIG. 12, in the photograph of the surface of the separator of Example 1, traces of adhesive application were observed.
[0151] On the other hand, as shown in FIG. 13, since no adhesive was used in manufacturing the electrode assembly of Comparative Example 1, no traces of adhesive application were observed in the photograph of the surface of the separator of Comparative Example 1.
[0152] 2. Resistance Assessment For the secondary batteries of Example 1 and Comparative Examples 1 to 3, the resistance values calculated using the voltage change (ΔV) measured when discharging at a 2.5C rate for 10 seconds at SOC 50% are shown in Table 1 below.
[0153] 3. Evaluation of life performance The secondary batteries of Example 1 and Comparative Examples 1 to 3 produced as described above were charged and discharged for 100 cycles at 45° C. under the following conditions, and the capacity retention rate after 100 cycles was evaluated.
[0154] *Charging and discharging conditions Charging: CC / CV mode; 0.33C; 4.2V, 1 / 20C cut-off Discharge: CC mode; 0.33C; 2.5V cut-off
[0155] The capacity retention rate was defined as the value obtained by dividing the discharge capacity at the 100th cycle by the discharge capacity at the first cycle under the above experimental conditions. The results are shown in Table 1 below.
[0156] 4. Cell Stiffness Measurement In a 3-point bending test, a force was applied downward at the center of each secondary battery at a speed of 10 mm / min, resulting in a displacement of 2 mm, and the stress value was measured. A preload of 30 gf was applied, the experiment was conducted at room temperature, and the stress value was measured using a universal testing machine (UTM). The results are shown in Table 1 below.
[0157] 5. Nail penetration test A metal nail having a diameter of 3.0 mm was dropped onto the fully charged lithium secondary batteries manufactured in Example 1 and Comparative Examples 1 to 3 at a speed of 800 mm / min, and a thermocouple was attached to the surface of the secondary batteries to evaluate whether they ignite.
[0158] The experiment was carried out three times in total, and if no fire occurred, it was rated as Pass. The results are shown in Table 1 below.
[0159] [Table 1]
[0160] Referring to Table 1, it can be seen that the secondary battery of Example 1 according to the present invention simultaneously exhibits excellent effects of reducing resistance, improving lifespan, increasing cell rigidity, and improving safety.
[0161] On the other hand, in Comparative Example 1, although the resistance is at the same level as in Example 1, it can be confirmed that the cell rigidity is reduced, the safety is reduced, and a decrease in the life performance occurs.
[0162] In addition, Comparative Example 2 has excellent cell rigidity, but because a separator containing a large amount of binder and a gel polymer electrolyte are used, resistance increases compared to Example 1, and life performance is significantly reduced.
[0163] In the case of Comparative Example 3, the resistance was somewhat lower than that of Example 1, but the cell rigidity was significantly reduced, and in particular, all of the cells ignited during the nail penetration test, which confirmed that this was very unsafe. [Explanation of symbols]
[0164] 10 Secondary battery 100 electrode assembly U base unit 110 1st electrode 120 2nd electrode 130 Separator 130a First separator 130b Second separator 131 Porous substrate 132a, 132b Ceramic coating layer 140, 141, 142 Adhesive marks 140a Applied adhesive 200 Gel polymer electrolyte 300 Battery Case 310 Cover 400, 500 electrode tab 600 nozzles
Claims
1. The battery includes an electrode assembly, a gel polymer electrolyte, and a battery case that houses the electrode assembly and the gel polymer electrolyte, The electrode assembly includes a plurality of electrodes and a plurality of separators, The plurality of electrodes are stacked vertically, Each of the plurality of separators is interposed between the stacked electrodes, The separator includes a porous substrate and a ceramic coating layer disposed on both sides of the porous substrate; The ceramic coating layer comprises 92% by weight or more and less than 100% by weight of inorganic particles and more than 0% by weight and 8% by weight or less of a binder.
2. 2. The secondary battery according to claim 1, wherein the ceramic coating layer comprises 93% to 98% by weight of inorganic particles and 2% to 7% by weight of a binder.
3. The secondary battery according to claim 1 , wherein the binder comprises an acrylic binder.
4. 4. The secondary battery according to claim 3, wherein the acrylic binder comprises at least one selected from the group consisting of a copolymer of ethylhexyl acrylate and methyl methacrylate; polymethyl methacrylate; polyethylhexyl acrylate; polybutyl acrylate; polyacrylonitrile; and a copolymer of butyl acrylate and methyl methacrylate.
5. The secondary battery according to claim 1 , wherein the ceramic coating layer has a thickness of 0.1 μm to 10 μm.
6. 2. The secondary battery according to claim 1, wherein the separator has a thickness of 1 μm to 20 μm.
7. The secondary battery according to claim 1 , wherein the gel polymer electrolyte is a cured product of a gel polymer electrolyte composition containing a lithium salt, a polymerization initiator, and an oligomer compound.
8. 8. The secondary battery according to claim 7, wherein the oligomer compound is contained in the gel polymer electrolyte composition in an amount of 1% by weight to 20% by weight.
9. 8. The secondary battery according to claim 7, wherein the oligomer compound includes at least one selected from the group consisting of a fluorine-based oligomer, a polycarbonate-based oligomer, and a polysiloxane-based oligomer.
10. The electrode assembly is manufactured by applying an adhesive to a surface of at least one of the electrode and the separator, and adhering the electrode and the separator to each other, 2. The secondary battery according to claim 1, wherein the adhesive is removed by housing the gel polymer electrolyte and the electrode assembly in the battery case, and a trace of adhesive remains on a surface of at least one of the electrodes and the separator.
11. The secondary battery according to claim 10 , wherein the adhesive is applied in a plurality of patterns spaced apart from one another.
12. The secondary battery according to claim 10 , wherein an area where the adhesive is applied is more than 0% and not more than 1% of an area of a surface where the separator and the electrode are in contact with each other.
13. the electrodes include a first electrode and a second electrode; The secondary battery according to claim 1 , wherein the first electrodes and the second electrodes are alternately stacked.
14. housing the electrode assembly in a battery case; injecting a gel polymer electrolyte composition into the battery case; curing the gel polymer electrolyte composition; and sealing the battery case. The electrode assembly includes a plurality of electrodes and a plurality of separators, The plurality of electrodes are stacked vertically, Each of the plurality of separators is interposed between the stacked electrodes, The separator includes a porous substrate and a ceramic coating layer disposed on both sides of the porous substrate; The ceramic coating layer comprises 92 wt % or more and less than 100 wt % of inorganic particles and more than 0 wt % and 8 wt % or less of a binder.
15. The method of claim 14, wherein the electrode assembly is manufactured by applying an adhesive to at least one surface of the electrode and the separator, and adhering the electrode and the separator to each other.
16. The method of claim 15, wherein the adhesive is applied in a plurality of patterns spaced apart from each other.
17. The method for producing a secondary battery according to claim 15, wherein the adhesive is dissolved and removed by a gel polymer electrolyte composition injected into the battery case.
18. The method for producing a secondary battery according to claim 17 , wherein after the adhesive is removed, traces of the adhesive remain on a surface of at least one of the separator and the electrode.
19. The method for producing a secondary battery according to claim 15 , wherein the adhesive is an acrylate adhesive.
Citation Information
Patent Citations
A battery cell containing a gelled electrolyte component in the pores of a separator membrane constituting an electrode assembly
JP2018521483A
Gel polymer electrolyte composition and lithium secondary battery containing gel polymer electrolyte formed therefrom
JP2021512461A
Separator for secondary cell
WO2013151144A1
Lithium ion secondary battery
WO2018079353A1